Revisiting the effect of statutory pension ages on the Participation Rate (Public Sector Economics - submission site, 2021)
Cross-country estimation work consistently finds that coefficients on statutory pension ages are positive and highly statistically significant in explaining labour force participation at older ages. However, the estimated effects are surprisingly modest when translated into the implied effect on the average effective age of retirement, which typically only increases by about 2 months for every year by which the statutory retirement age increases. This paper shows that grouping countries with similar pension systems, allowing for time heterogeneity and introducing other modelling choices, can improve the estimates of the effect of changes to the pension system. In countries in which there are alternative early retirement pathways or voluntary private pension systems, the effect of changes in statutory retirement ages tends to be dampened. However, for other countries, the effect of changes in statutory pension ages can be around two to three times larger than the typical finding from pooled country estimations.